Hubungan Kelengkapan Alat Praktek Siswa Konsentrasi Keahlian Teknik Kendaraan Ringan dengan Kesiapan Siswa untuk Melaksanakan Praktek Kerja Industri di SMK Negeri 1 Padang - Busman, Yezi Akhiardi; Martias, Martias (MASALIQ, 2024)
This study aims to analyze the relationship between the completeness of practical tools and student readiness to carry out Industrial Work Practices (Prakerin) at SMK Negeri 1 Padang. A quantitative approach with a correlational method was used in this study, with a sample of 56 students from the Light Vehicle Engineering (TKR) department selected using purposive sampling technique. Data were collected through questionnaires measuring the completeness of practical tools and student readiness, and analyzed using Pearson correlation test and simple linear regression. The results showed that there was a positive and significant relationship between the completeness of practical tools and students' readiness to carry out Prakerin, with a correlation coefficient of 0.70. Regression analysis revealed that the completeness of practical tools contributed 49% to student readiness, while the other 51% was influenced by other factors. The implications of this study indicate the importance of providing adequate practical tools to improve student readiness to face the industrial world. Good completeness of practical tools can help students master practical skills and increase their confidence in a real work environment.